(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
A country’s need for well-maintained road networks and appropriate road maintenance procedures is crucial for facilitating socioeconomic progress. However, the majority of federal highways are not in excellent shape, and more than one-third of them are in extremely poor or poor condition, which makes them unsafe for driving. The focus of this study was on identifying the current issues with road maintenance and evaluating the overall consequences of inadequate road maintenance on road function. The preservation of the investment made in the highway system as well as the comfort and safety of the road user were found to depend heavily on the proper design, routine inspection, and maintenance of the drainage system.. All different kinds of distresses have been categorized. For varying degrees of each suffering, there are several causes and treatments. It is crucial to recognize and fix the flaws in the current highway maintenance procedures and system. In this study, impacting factors such as cracks and cracking patterns, roughness, rut depth, potholes, and deflections were taken into account. The severity levels of the aforementioned factors have been used to categorize them. Therefore, it is advised that when doing any road maintenance, all concerned parties pay full attention to the most severe (acknowledged) issues in order to address the issues and lessen their impacts.